Phenylalanine promotes alveolar macrophage pyroptosis via the activation of CaSR in ARDS - Tang, Yiding; Yu, Yue; Li, Ranran; Tao, Zheying; Zhang, Li; Wang, Xiaoli; Qi, Xiaoling; Li, Yinjiaozhi; Meng, Tianjiao; Qu, Hongping; Zhou, Mi; Xu, Jing; et al. (Frontiers in Immunology, 2023)
Acute respiratory distress syndrome (ARDS) carries a high mortality in Intensive Care Unit (ICU) patients. Overwhelming inflammation is considered to be the internal cause. Our previous study indicated potential correlation between phenylalanine and lung injury. Administration of phenylalanine was proved to induce inflammation by enhancing the innate immune response and releasing of pro-inflammatory cytokines. Alveolar macrophages (AMs) can respond to stimuli via synthesis and release of inflammatory mediators through pyroptosis, one form of the programmed cell death acting through nucleotide-binging oligomerization domain (NOD)-like receptors(NLR) Protein 3 (NLRP3) signaling pathway, resulting in the cleavage of Caspase-1 and gasdermin D (GSDMD) and the release of IL-1β and IL-18, aggravates lung inflammation and injury in ARDS. In this article, we demonstrated that phenylalanine promoted the pyroptosis of AMs, thus exacerbating lung inflammation and ARDS lethality in mice. We further revealed that phenylalanine initiated NLRP3 pathway by activating calcium-sensing receptor (CaSR). Thus, our findings have uncovered a critical mechanism of phenylalanine in the context of ARDS which may be a new treating target of ARDS.